L’approche fonctionnelle de discours: traitement de l’information au niveau supraphrastique - Miczka, Ewa (Neophilologica, 2005)
In her article Ewa Miczka presented a model of discourse as a multidimensional object and a conception of understanding discourse as the process of creation of its representation. Six domains of this representation - informational, ontological, axiological, functional, expressional and metatextual ones correspond with the previously distinguished dimensions of discourse. The author focused her attention on the issue of (re)constructing the informational domain in the creation of discursive representations.